Feasibility of expansion of irrigated farming in Yuma county, Arizona - Blackledge, Glenn E., author; Burdick, R. T. (Raymond Terry), 1889-1982, advisor; Moorhouse, L. A. (Llewellyn Alexander), committee member; Leonard, Warren H., 1900-, committee member; Kezer, Alvin, 1877-, committee member; Avery, George T., committee member (Colorado State University. Libraries, 1940)
To view the abstract, please see the full text of the document.
Keywords: Irrigation -- Arizona -- Yuma County; Agriculture -- Arizona -- Yuma County